Assessing The Impact of Covid-19 E-Learning on Nursing Students: An Investigation into Techno-Stress (Journal of Namibian Studies : History Politics Culture, 2023)
The COVID-19 pandemic has brought about unprecedented changes in the educational landscape, necessitating a rapid shift towards e-learning platforms. This study sought to explore the techno-stress experienced by Nursing students at the University of Eastern Philippines (UEP) during e-learning amid the COVID-19 pandemic, as well as the coping mechanisms employed to mitigate its impact. The research was conducted with a focus on Level 3 and Level 4 Nursing students officially enrolled. The objectives of the study were to determine the demographic profile of the respondents in terms of age, sex, and year level and assess the level of techno-stress experienced by the students. Research questionnaires were utilized to gather the necessary data. The collected data were subsequently tallied, tabulated, presented, analyzed, and interpreted using percentage, weighted mean, and chi-square test methodologies. The findings of this study shed light on the techno-stressors faced by Nursing students in the context of e-learning during the COVID-19 pandemic. The analysis revealed valuable insights into the coping strategies employed by the respondents to manage these challenges. By understanding the factors contributing to techno-stress and exploring effective coping mechanisms, this research contributes to the broader understanding of the impact of the pandemic on education. Overall, this investigation serves as a significant step in assessing the impact of COVID-19 E-Learning on Nursing Students, highlighting the importance of addressing techno-stress and promoting adaptive coping strategies to enhance the overall well-being and academic performance of students in the ever-evolving landscape of virtual education.